Meningkatan Kemampuan Siswa Menulis Teks Naratif Bahasa Inggris Menggunakan Media Gambar Berseri Pada Siswa Kelas VIII SMP Negeri 8 Makassar - Elisabet Rante Sulu'; Nurfaizah Sahib; Muliati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
The objective of this research was to find out the using of serial image media can improve students’ ability writing in English narrative text. The researcher used the pre-experimental one group pre-test, post-test research. The total population of class VIII was 395 students amounting eleven classes, The research sample was class VIII.5 which consist 35 student participants. The research was conducted by giving treatment and succeeded in improving students’ ability writing narrative text in several element consisting of content, organization, vocabulary, grammar and mechanic. The treatment was carried out using serial image media as a medium in learning writing. After conducted the research, the researcher analyzed the data using IBM SPSS statistics 24. There was a significant increase in the using serial image media in writing narrative text at class VIII.5.The result of the mean writing score on the pre-test was 59.40, after the researcher gave treatment using serial image media, it turned out that the score of students’ writing in the post-test increased to 78.66. Therefore, the using of serial image media can improve students at class VIII.5 of SMPN 8 Makassar in ability writing narrative text. Key Words : Serial Image Media, Writing Ability, Narrative Text